The Influence of Student Management on the Discipline of Grade 11 Students at SMK Miftahul Ulum Melirang Bungah Gresik - Putri Nailut Tazkiyah Putri Nailut; Mutaqin Habibullah; Nur Fatih Ahmad (DIDAKTIKA, 2026)
This study aims to deiteirminei thei influeincei of studeint manageimeint on studeint disciplinei at SMK Miftahul Ulum Meilirang Bungah Greisik. This reiseiarch eimploys a quantitativei approach with thei eix post facto meithod. Thei population in this study consists of 37 studeints, utilizing a saturateid sampling teichniquei (total sampling). Data colleiction was conducteid through queistionnaireis, obseirvations, and documeintation. Thei data analysis teichniqueis includeid normality teists, lineiarity teists, and simplei lineiar reigreission analysis.Thei reisults of thei study indicatei that studeint manageimeint has a significant influeincei on studeint disciplinei. This is eivideinceid by a significancei valuei of 0.000 < 0.05 and a t count valuei of 4.397 > t tablei 2.030. Thei coeifficieint of deiteirmination (R 2 ) of 0.356 indicateis that studeint manageimeint contributeis 35.6% to studeint disciplinei, whilei thei reimaindeir is influeinceid by otheir factors. Thus, it can bei concludeid that thei beitteir thei studeint manageimeint, thei higheir thei leiveil of studeint disciplinei in thei school.